IEEE Nuclear Science Symposium Conference Record, 2005
DOI: 10.1109/nssmic.2005.1596931
|View full text |Cite
|
Sign up to set email alerts
|

Detailed Monte Carlo Investigation of a Proton Computed Tomography System

Abstract: Proton therapy is a precise form of radiation therapy and thus it requires accurate quality control of patients treatment. Protons may be more suitable than conventional x rays for this task since the relative electron density distribution can be measured directly with proton Computed Tomography (pCT). However, proton CT has its own limitation. The main limit is that of spatial resolution limited by Multiple Coulomb Scattering of proton inside the body of patient. In order to improve spatial resolution we need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…They used BEAMnrc to model a kV x-ray In the field of proton therapy, proton CT (pCT) is being suggested to directly obtain proton stopping powers, reducing one of the largest sources of uncertainty in determining the dose distributions: the conversion of CT-HU to proton stopping power or material composition (Schulte et al 2005). Cuttone et al reported MCSs with the Geant4 code for a proton tracking system to obtain the most likely paths (MLPs) of single protons in the object as shown in figure 14 (Cuttone et al 2005). The system consisted of multiple layers of silicon detectors with a thickness of 1 mm and a CsI calorimeter at the end to predict the proton paths and to measure the energy loss of the proton, respectively.…”
Section: Mcss For Imaging Devices Used In Radiotherapy 221 Computed T...mentioning
confidence: 99%
“…They used BEAMnrc to model a kV x-ray In the field of proton therapy, proton CT (pCT) is being suggested to directly obtain proton stopping powers, reducing one of the largest sources of uncertainty in determining the dose distributions: the conversion of CT-HU to proton stopping power or material composition (Schulte et al 2005). Cuttone et al reported MCSs with the Geant4 code for a proton tracking system to obtain the most likely paths (MLPs) of single protons in the object as shown in figure 14 (Cuttone et al 2005). The system consisted of multiple layers of silicon detectors with a thickness of 1 mm and a CsI calorimeter at the end to predict the proton paths and to measure the energy loss of the proton, respectively.…”
Section: Mcss For Imaging Devices Used In Radiotherapy 221 Computed T...mentioning
confidence: 99%